Effects of sulfur dioxide and particulate matter pollution on hospital admissions for hypertensive cardiovascular disease: A time series analysis - Nouri, Fatemeh; Taheri, Marzieh; Ziaddini, Mahdi; Najafian, Jamshid; Rabiei, Katayoun; Pourmoghadas, Ali; Shariful Islam, Sheikh Mohammed; Sarrafzadegan, Nizal (Frontiers in Physiology, 2023)
Air pollution is a major environmental risk factor and the leading cause of disease burden with detrimental effects on the cardiovascular systems. Cardiovascular diseases are predisposed by various risk factors, including hypertension, as the most important modifiable risk factor. However, there is a lack of sufficient data concerning the impact of air pollution on hypertension. We sought to study the associations of short-term exposure to Sulfur dioxide (SO2) and particulate matter (PM10) with the number of daily hospital admissions of hypertensive cardiovascular diseases (HCD) in Isfahan, one of the most polluted cities in Iran, between March 2010 to March 2012. All hospitalized patients in the period of the study were recruited with the final diagnosis of HCD based on the International Classification of Diseases 10 (codes: I10-I15) from 15 hospitals. The 24-hour average concentrations of pollutants were obtained from 4 monitoring stations. In addition to single- and two-pollutant models, we used Negative Binomial and Poisson models with covariates of holidays, dew point, temperature, wind speed, and extracted latent factors of other pollutants controlling for multi-collinearity to examine the risk for hospital admissions for HCD affected by SO2 and PM10 exposures in the multi-pollutant model. A total of 3132 hospitalized patients (63% were female) with a mean (standard deviation) age of 64.96 (13.81) were incorporated in the study. The mean concentrations of SO2 and PM10 were 37.64 μg/m3 and 139.08 μg/m3, respectively. Our findings showed that a significantly increased risk of HCD-induced hospital admission was detected for a 10 μg/m3 increase in the 6-day and 3-day moving average of SO2 and PM10 concentrations in the multi-pollutant model with a percent change of 2.11% (95% confidence interval: 0.61 to 3.63%) and 1.19% (0.33 to 2.05%), respectively. This finding was robust in all models and did not vary by gender (for SO2 and PM10) and season (for SO2). However, people aged 35-64 and 18-34 years were vulnerable to SO2 and PM10 exposure-triggered HCD risk, respectively. In conclusion, this study supports the hypothesis of the association between short-term exposure to ambient SO2 and PM10 and the number of hospital admissions due to HCD.